Social Influence and Student Choices: Exploring Online Word-of-Mouth, Brand Trust, and Purchase Intentions in Malaysia - Daisy Mui Hung Kee; Christina Yeoh Zi Yi; Chow Wan Ting; Dakshayani A/P Jaganathan; Dong Kaiyuan (AIBPM Publisher, 2025)
This study investigates how social influence, online word of mouth (WOM), and brand trust shape the purchase intentions of Malaysian university students, with a focus on the mediating role of brand trust. Using a quantitative design, an online survey of 152 students was analyzed with structural equation modeling (SEM). The findings show that purchase intention is positively predicted by perceived social influence (? = 0.448), online WOM (? = 0.310), and brand trust (? = 0.211), supporting H1–H3. Brand trust is also positively predicted by social influence (? = 0.320) and online WOM (? = 0.519), supporting H4–H5 and indicating a mediating pathway from online WOM and social influence to purchase intention via brand trust. The explained variance is R² = 0.019 for purchase intention and R² = 0.574 for brand trust. Overall, the results confirm that online WOM, social influence, and brand trust are key drivers of student purchase intention, with online WOM exerting the strongest effect on brand trust. These insights contribute to the literature on digital consumption and offer practical guidance for marketers and brands targeting Malaysian students to strengthen trust-building and WOM-based engagement strategies.